(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The internal rate of return (IRR) is one of the profitability analysis indicators which are often used in project evaluation. But it has many flaws. There are three main following flaws. The first flaw is that the implied reinvestment rate assumption of internal rate of return is unreasonable. The second flaw is that solving IRR is difficult. The third flaw is that there may be multiply IRRs or no IRR for unconventional cash flow projects. Many scholars have studied it and put forward many improved methods. Modified internal rate of return (MIRR) is one of the methods to improve IRR. This article compares IRR and MIRR. Solving MIRR is relatively simple. And it is important that MIRR is unique. An example is given to demonstrate how to compute MIRR. The reinvestment rate of MIRR usually equals to the project’s cost of capital. But the value of MIRR is affected by the discount rate that often is minimum attractive rate of return(MARR).Like the IRR, ranking problem of the MIRR still exists. So MIRR is only suitable in single project evaluation. It can not be applied in mutually exclusive project evaluation. Finally an example is given to verify the correctness.